تحدید بعض خصائص أغشیة أكسید النیكل ) (NiOالمطعم بالحدید )(F - مصباحي, الطاهر; دقة, عبد الله (My University, 2017)
This work includes the study of the structural, electrical and optical characteristics of pure nickel oxide (NiO) thin films prepared from different molar concentrations of solution of nickel nitrate (Ni(NO3)2.6H2O) and another doped with iron (Fe) with the different volume percentages (3-6-9-12-15 %) of the solution of Iron nitrate (FeN3O9.9H2O), where the deposition of thin films of nickel oxide (NiO) on glass substrates done under the temperature (500 oC) by the pyrolytic spray technique. The results of X-rays diffraction showed that the films prepared have a cubic crystal structure in a dominant direction (111), and it was noted that there is an increase in light transmission due to doping up to (85%), on the other hand, the results of tests (FTIR) showed the emergence of chemical bonds (Ni-O) and (Fe-O), which appear in the frequency range (505-443 cm-1), whereas the surface resistance showed a remarkable increase after doping, and the value of energy of band gap of pure films was about (3.69 V), but in the case of the iron-doped films the energy of band gap took the values between (3,41eV) to (3.69 V) .Ce travail s'est intéressé à l'étude des caractéristiques structurelles, électriques et optiques des couches minces d'oxyde de nickel (NiO) pur, préparé à partir de différentes concentrations molaires de solution de nitrate de nickel(Ni (NO3)2.6H2O)et d'autres dopées fer (Fe) par des pourcentages volumiques (3-6-9-12- 15%) du nitrate de fer (FeN3O9.9H2O), où le dépôt des couches minces d'oxyde de nickel (NiO) sur des substrats de verre sous la température (500 o C) par la technique de spray pyrolytique, les résultats de diffraction des rayons X ont montré que les couches minces préparées ont une structure cristalline cubique et une direction dominante (111), une augmentation de la transmission de la lumière à cause du dopage a été notée , elle a atteint 85%, d'autre part, les résultats des tests (FTIR) ont montré l'émergence des liaisons chimiques (Ni-O et Fe-O), qui apparaissaient dans la gamme de fréquences (505-443 cm-1), la résistance de surface a connu une augmentation notable après le dopage, l'énergie de gap des couches pures a atteint une valeur max de 3,69 eV, variant de 3,41eV jusqu'à 3,69 eV dans le cas des couches dopées fer
مذكرة ماستر فيزياء
Keywords: thin films, nickel oxide, pyrolytic spray technique, X-ray diffraction, (FTIR); couches minces, oxyde de nickel, technique de spray pyrolytique, diffraction des rayons X, (FTIR).